2014
DOI: 10.1155/2014/648715
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathological Aspects of ExperimentalTrypanosoma cruziReinfections

Abstract: Chagas disease is caused by Trypanosoma cruzi infection. Besides the host-related factors, such as immune response and genetic background, the parasite, strain, and occurrences of reinfection episodes, may influence disease outcome. Our results demonstrate that both the primary infection and the reinfection with the Colombiana strain are connected with lower survival rate of the mice. After reinfection, parasitaemia is approximately ten times lower than in primary infected animals. Only Colombiana, Colombiana/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Qualitative analysis classified infiltrate as predominantly mononuclear (macrophages and lymphocytes) or polymorphonuclear (neutrophils and eosinophils), according to the cellular type observed in more than 50% of the infiltrate. Semiquantitative analysis classified the inflammatory infiltrate in mild (involvement < 25% of the tissue), moderate (25%–50% of the tissue), or severe (involvement > 50% of the tissue) [25].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative analysis classified infiltrate as predominantly mononuclear (macrophages and lymphocytes) or polymorphonuclear (neutrophils and eosinophils), according to the cellular type observed in more than 50% of the infiltrate. Semiquantitative analysis classified the inflammatory infiltrate in mild (involvement < 25% of the tissue), moderate (25%–50% of the tissue), or severe (involvement > 50% of the tissue) [25].…”
Section: Methodsmentioning
confidence: 99%
“…Our group had already pointed out that infected and reinfected animals with Colombian strain present a modulation of immune response leading to higher production of proinflammatory cytokines, such as IFN- γ and TNF- α , resulting in marked myocarditis and lower survival rate [25]. As Balb/c mice are usually good IL-4 producers [26] and due to IL-4 relevance in modulating response against infectious and parasitic agents, including chagasic cardiomyopathy, IL-4 −/− knockout animals were used to analyze if this cytokine has any influence on immune response modulation in mice infected with T. cruzi Colombian strain, which has marked myotropism in acute phase.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the generation of a parasitaemia following initial infection, with subsequent infections generating lower [21] or no parasitaemias in mice, and the observation of no significant increase in tissue damage in reinfected dogs independent of isolates utilised [41], are indicative of host immune protection. Conversely, other studies investigating reinfection have demonstrated a failure to protect mice [42], with the observation of an increased parasitaemia [30] and an increase in the severity of cardiac alterations and disease progression [20,43]. Subsequently, these alterations may lead to death of the host [31].…”
Section: Effects Of Reinfectionmentioning
confidence: 99%
“…This genetic heterogeneity means that dissimilar outcomes from reinfection experiments may reflect differences in parasite virulence or in the host immune response to the different parasite genotypes utilised. While the use of reference or highly utilised genotypes such as the Y [31,43], Tulahuen [20] and Colombian strains [45] in previous reinfection studies was useful in order for comparisons to be drawn between studies, more studies involving diverse and previously uncharacterised genotypes are also required to expand our knowledge.…”
Section: Effects Of Reinfectionmentioning
confidence: 99%
“…A sustained inflammatory response featuring progressive tissue damage and fibrosis-related repair leads to chronic cardiac disability due to destruction and rearrangement of cardiomyocytes, microvasculature damage, and contractile alterations (12). Murine reinfections by T. cruzi are associated with cardiac damage and higher levels of inflammatory cytokines (13). In humans, the cellular immune response pattern seems to be related, at least in part, to the clinical forms.…”
mentioning
confidence: 99%